Recombinant α-Klotho Protein Alleviated Acute Cardiorenal Injury in a Mouse Model of Lipopolysaccharide-Induced Septic Cardiorenal Syndrome Type 5 - Xi Liu; Yangyang Niu; Xiaoqin Zhang; Yingying Zhang; Ying Yu; Jieli Huang; Jiangtao Li; Chen Yu (Analytical Cellular Pathology)
Background and Aims. Klotho is an aging-suppressor gene mainly expressed in the renal tubules. The klotho gene encodes the α-klotho protein, which has many functions. Previous studies have found that α-klotho protein has a cardiorenal protective function. α-Klotho deficiency renders the kidney more susceptible to injury and results in cardiovascular calcification and left ventricular hypertrophy in chronic kidney disease. However, the role of α-klotho in acute heart injury and acute kidney injury with sepsis remains unknown. This study aimed to investigate the effects and mechanisms of α-klotho in septic cardiorenal injury. Methods. Male 8-week-old C57BL/6 mice were randomly assigned to the control group, lipopolysaccharide (LPS; 10 mg/kg) group, LPS (10 mg/kg)+α-klotho (0.01 mg/kg) group, and LPS (10 mg/kg)+α-klotho (0.02 mg/kg) group. Recombinant α-klotho was intraperitoneally injected an hour before LPS injection. Mice were euthanized at 24 h after LPS injection. The serum troponin, brain natriuretic peptide (BNP), neutrophil gelatinase-associated lipocalin (NGAL), and creatinine levels were measured in all groups at 24 h. Biomarkers of mice heart apoptosis, inflammation, oxidative stress, and endoplasmic reticulum stress, such as caspase-3, interleukin 1 (IL-1), reactive oxygen species (ROS), and glucose-regulated protein 78 (GRP78), were also measured. Results. α-Klotho was mainly expressed in mice kidneys and was undetectable in the control mice hearts. α-Klotho substantially decreased after LPS injection. In the LPS group, the serum troponin levels significantly increased as early as 6 h (p<0.05) after LPS injection, while the BNP, NGAL, and creatinine levels significantly increased at 24 h (p<0.05). Pretreatment with α-klotho significantly ameliorated acute cardiorenal injury. In the LPS+α-klotho (0.01 mg/kg) group, the levels of apoptosis, inflammation, and oxidative stress were decreased, while the level of endoplasmic reticulum stress was elevated. Conclusions. α-Klotho significantly alleviates acute cardiorenal injury in LPS-induced septic cardiorenal injury due to the inhibition of apoptosis, inflammation, and oxidation, as well as the regulation of endoplasmic reticulum stress levels.